Implementation of Information Services Through Self Control Strategies in Overcoming Smartphone Addiction in Students - Ahmad Zaki Ilman Nasution; Nurussakinah Daulay (Universitas Pendidikan Ganesha, 2023)
Smartphone use can lead to smartphone addiction behavior. Smartphone addiction can occur if a person continuously and excessively uses it, which will harm him. Therefore, this study aims to analyze whether applying information services through self-control strategies can overcome smartphone addiction in students. Quantitative methods and experimental approaches, known as quasi-experiments, are used in this type of research. The design used was the pretest-posttest control group design; in this design, the experimental group received treatment, while the control group received no treatment. The samples taken were 34 students who were divided into two groups. The experimental group consisted of 17 students, and the control group consisted of 15 students. Data was collected through a structured questionnaire given to students to measure smartphone addiction. Data were analyzed using inferential statistics. The results obtained found differences between the two groups. There was a decrease in smartphone addiction in the experimental group, while the control group experienced an increase in smartphone addiction. This means that applying information services through this self-control strategy influences smartphone addiction in students.